Analisis Pengaruh Karakteristik Perusahaan dan Ekonomi Makro Terhadap Return Saham (Studi Empiris Pada Perusahaan Real Estate dan Property) - Frihardina Frihardina; Rossje V Suryaputri (Jurnal Magister Akuntansi Trisakti, 2015)
Real estate and property is one of industry that has developed very rapidly. Investors assess that property is not only about human need but also become a good investment for the future. The increase of real estate and property’s company each year on Indonesia Stock Exchange shows that this investment is attracted investors to place their fund to get more return. This study aimed to analyze the effect of financial performance (ROE), size, systematic risk, inflation rate and exchange rate on stock returns of real estate and property company listed on the Indonesia Stock Exchange in observations from 2009-2013 using multiple regression method with SPSS 20. The data used are secondary data from Jakarta Stock Exchange (JSX) Yearly Statistics, Statistik Ekonomi dan Keuangan from Bank Indonesia, official website of Bank Indonesia, Yahoo Finance on 2009-2013. Population research consist of 47 listed companies and the end with purposive sampling method this research employed an empirical study by using 26 companies. The hypothesis test result showed that systematic risk have positive influence to stock return and inflation rate have negative influence to stock return, on the other hand there is no significantly influence for financial performance (ROE), size’s company and exchange rate.